Influence of laser power on bonding strength for low purity copper wire bonding technology - Singh, Gurbinder; Haseeb, A.S. Md. Abdul (Elsevier, 2019)
The drive for improving copper wire bonding has been more rampant with continued rise in gold prices. The global increase in gold price directly resulted the semiconductor packaging industry to rapidly replace gold as a medium of interconnection to copper wire. This is a cost effective solution for creating viable interconnections for integrated circuit packaging. However, through past research it is well known the hardness of copper wire is significantly higher compared to gold wire and the usage of copper poses various challenges in electronic packaging. These challenges, resulting from the usage of copper wire is primarily due to the high hardness of copper. Higher hardness of copper as compared to gold will require higher bonding force and ultrasonic energy to create bonding to the bond pads. The higher bonding force makes copper wire bonding unsuitable for fragile structures and possible damage to underlying circuitry. Past research has also exhibited the hardness of copper wire decreases as the purity levels increase, however the usage of higher purity copper wires in high volume manufacturing may significantly increase manufacturing cost. This research therefore investigates the application of laser assisted heating for enabling improved copper wire bonding strength and improved grain structures for low purity copper wires. Experimentations were conducted accordingly on three copper wire purity types, 99.9% purity (3 N), 99.99% purity (4 N) and 99.999% purity (5 N) copper wires, so as to evaluate the impact of laser assisted heating on various copper purity levels. The result of this study shows laser assisted heating is able to improve the bonding strength and improve the grain structure by means of reduced columnar grains for copper wires with lower purity levels. It is shown, higher as-bonded ball shear strengths with fewer columnar grains were observed when the highest laser heating intensity was applied. The results of this study can be helpful for integrated circuit packaging especially to enable interconnections using copper wire materials with lower purity levels, enabling a more cost effective manufacturing. © 2019 Elsevier B.V.